Challenges and opportunities with H-2B visas: can luxury resorts survive without them?. Issue 1 (25th November 2020) - Kubickova, Marketa; Neal, Rebecca
Abstract : Purpose: This study aims to provide a deeper look into why luxury resorts engage in the H-2B visa program and the opportunities and challenges from the human resources employee perspective. Adequate staffing is a well-documented challenge for luxury resorts due to their location, seasonality and access to qualified labor. Many resorts turn to the H-2B non-immigrant visa to mitigate the issue. Design/methodology/approach: This study consists of in-depth interviews with human resource employees. An additional survey centering on descriptive statistics, the level of engagement, cost and experience with H-2B visa programs was collected. Findings: The findings of this study provide a deeper understanding why luxury resorts use H-2B employees in their operations. The results shed a deeper light on issues centering around the H-2B visa process, its uncertainty, cost and complexity. Practical implications: Temporary H-2B workers are essential to the success of resort operation. Collaboration between the resort management and government agencies is essential as strategic solutions must be implemented. Resorts must explore diversified recruitment opportunities and the use of technology while keeping human labor in the center of its core operation. Originality/value: The first exploratory study providing a deeper look into the many challenges' luxury resorts face when using the H-2B visa program from the human resources employee perspective. A call for change is being made as the respondents established the need for H-2B workers, however, the system in place makes it difficult to obtain such employees and to continue resort operations.